Isolation of a Complex Formed Between Acinetobacter baumannii HemA and HemL, Key Enzymes of Tetrapyrroles Biosynthesis - Nardella, Caterina; Boi, Dalila; di Salvo, Martino L.; Barile, Anna; Stetefeld, Jörg; Tramonti, Angela; Contestabile, Roberto (Frontiers in Molecular Biosciences, 2019)
Plants, algae and most bacteria synthesize 5-aminolevulinic acid (ALA), the universal precursor of tetrapyrroles such as heme, chlorophyll and coenzyme B12, by a two-step transformation involving the NADPH-dependent glutamyl-tRNA reductase (HemA), which reduces tRNA-bound glutamate to glutamate-1-semialdehyde (GSA), and the pyridoxamine 5’-phosphate-dependent glutamate-1-semialdehyde-2,1-aminomutase (HemL), responsible for the isomerization of GSA into ALA. Since GSA is a very unstable compound at pH values around neutrality, the formation of a HemA-HemL complex has been proposed to occur, allowing for direct channeling of this intermediate from HemA to HemL. Experimental evidence of the formation of this complex has been obtained with the enzymes from Escherichia coli and Chlamydomonas reinhardtii. However, its isolation has never been attained, probably because HemA is degraded when intracellular heme accumulates. In this work, we devised a co-expression and co-purification strategy of HemA and HemL from Acinetobacter baumannii, which allowed the isolation of the HemA-HemL complex. Our results indicate that HemA is stabilized when co-expressed with HemL. The addition of citrate throughout the expression and purification procedure further promotes the formation of the HemA-HemL complex, which can be isolated in fair amount for functional and structural studies. This work lays the bases for a rational design of HemA-HemA inhibitors to be developed as antibacterial agents against A. baumannii, a multidrug resistant opportunistic pathogen responsible for a broad range of severe nosocomial infections.